Diseño de un sistema contable que permite optimizar legalmente la declaración del IVA en Ecuador - Díaz Montenegro, José (2010)
Most of Ecuador’s contributors don’t prepare a well elaborate tax credit application form for their IVA declarations, which lead them to give a payment that goes unnecessary above the actual value, due to the inadequate form filling. In this article, we can see that through the implementation of a simple accounting system, taxpayers can optimize their IVA declaration without breaking any current tax provision, even more, going side by side with our country’s established law.